Analisis Wacana Plesetan Pada Merk Obat-obatan - Siska Novia Anggara; Ulin Intan Saputri; Intan Dewitasari (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2019)
This study aims to determine the play discourse analysis on drug brands.The play language is considered a deviation from the language that isused by the community because it has unusual patterns and violateslanguage conventions. Unlawfulness has two possible assumptions,namely as commendable or as a disgraceful thing. The play language inmany speech situations emphasizes humor and humor, and is relaxed.The method used in this research is qualitative method. Qualitativemethods as a research procedure in which the descriptive data is in theform of a series of words in writing or verbally from someone andbehavior that can be observed. The application of this qualitative methodhas descriptive properties which mean the data that has been generatedin the form of a series of words in a form of quotation. The results of thisstudy indicate that in a play on the boat-drug brand has several differentmeanings or meanings for the readers.